STUDI KASUS IDENTIFIKASI KERUSAKKAN MESIN BERDASARKAN SINYAL GETARAN - Ramses Yohannes Hutahaean; Dikky Antonius (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
The machine maintenance strategy is very important in manufacturing, mining, and other industries so an appropriate maintenance strategy is needed based on industrial operating conditions. In this paper, a Proactive maintenance strategy is presented, in which this strategy requires the identification of vibrations, and the identification of vibrations is divided into two methods, there are the identification of vibrations in the time domain and the identification of vibrations based on the frequency domain. Identification in the time domain is usually done in analyzing gears because of so much noise in the frequency domain, while identification in the frequency domain is used to analyze vibrations in cases of unbalance, misalignment, bearing defects, cavitation, and damage to electric motors. This paper briefly presents the time domain and frequency domain differences and two case studies that happened on PT. Freeport Indonesia. The first case is the investigation of bearing damage to the conveyor using vibration signals in the frequency domain, while the second case is the investigation of gear damage using the time domain that occurs in the crusher.